Public Financing Model Through Long-Term Contractual Agreements for Public-Private Partnership Projects - Wulandari, Septi; Septian, Esa (PERSPEKTIF, 2024)
This research aims to analyze alternative models of public financing in the Public-Private Partnership (PPP) scheme involving the government and the corporate sector. This research utilizes a qualitative research method with a content analysis data collection methodology to examine the limitations and shortcomings of PPPs. The findings of this study indicate that Public-Private Partnerships (PPPs) have shown a persistent pattern of failure, leading to continuous renegotiation between the government and the private sector. The implementation of PPPs carries risks that can lead to a loss of public oversight of PPP initiatives. The government's lack of experience in making judgments that can carry political risk also plays a role. The PPP model sets a higher cost of capital, which causes the private sector to charge higher tariffs to customers, possibly resulting in a monopoly by private companies. PPPs have imposed a burden on the state and faced opposition to privatization due to a lack of understanding among parties involved in state-owned enterprises (SOEs). The government lacks transparency in decision-making regarding privatization and fails to provide adequate information to stakeholders involved in SOE privatization. Government decision-making on privatization lacks transparency and does not follow established processes and procedures.